PERSEPSI GURU TERHADAP PENERAPAN KONSEP CALISTUNG (BACA, TULIS, HITUNG) DI TK AR-RAUDHAH DESA KACE TIMUR, KEC. MENDO BARAT DAN TPA CERIA SPNF SKB KOTA PANGKALPINANG KELURAHAN TUA TUNU, KEC. GERUNGGANG - Riswan, Riswan (ICEJ : Islamic Childhood Education Journal, 2022)
The application of  calistung (read, write and count) is still a pro and contra, there are still many assumptions that calistung should not be applied and there are also those who think that it can be applied. Calistung learning is an important component that must be mastered by children. The calistung learning process must be based on the principle of early childhood learning, namely playing while learning.  Therefore, calistung learning cannot be given directly. This research uses descriptive qualitative research, data sources, taken from primary data and secndary data, this research technique is done through observation, interviews and documentation. While the data analysis techhniques used and datareduction, data presentation and conclusion drawingof the data obtained. The results showed that the teacher’s perception of the application of the concept of calistung (read, write and count) that calistung could be applied to early childhood by using the correct method and the use of media in learning activities how teachers apply calistung through number puzzle medi, latterpuzzle media, block media, and shirt buttons as well as the methods that are often used, among others, the playing method.